Performance Analysis and Identification of an Indirect Photovoltaic Thermal Dryer with Aluminum Oxide Nano-Embedded Thermal Energy Storage Modification - Sirin, Ceylin; Selimefendigil, Fatih; Öztop, Hakan Fehmi Fehmi (Mdpi, 2023)
In the current paper, different thermal energy storage unit-integrated photovoltaic thermal (PVT) air collectors with and without nanoparticles have been designed, fabricated and tested. Aluminum oxide nanoparticles have been integrated into the thermal storage unit to increase the performance of the PVT collector. The developed collectors have been tested in a drying application at two different mass flow rates. The major goals of this work are upgrading the performance of the PVT air collector by employing a nano-embedded thermal energy storage unit and analyzing the impacts of using nanoparticles in the latent heat storage unit in the PVT collector on the drying performance of the system. The drying time was reduced by approximately 15-22% by employing nanoparticles in the thermal storage unit. Moreover, overall exergy efficiency values were obtained in ranges of 12.49-14.67% and 13.64-16.06%, respectively, for modified and unmodified PVT air collectors. It should be indicated that the overall energy and exergy efficiencies of the PVT air collectors were improved in the ranges of 6.91-6.97% and 9.20-9.47%, respectively, by using nanoparticles in the thermal energy storage unit. The combination of increasing the flow rate and integrating nanoparticles into the storage unit improved the overall exergetic efficiency of the PVT air collector by 28.58%. The mean exergetic efficiency of the drying room was between 48.33 and 54.26%. In addition to the experimental analysis, dynamic models for thermal and exergy efficiencies of developed collectors were constructed by employing the system identification method.
Keywords: photovoltaic thermal; aluminum oxide; nanoparticles; thermal energy storage; drying; system identification